(untitled) (Jalalabad Medical Journal, 2025)
Salivary gland tumours represent widespread varieties of tumours due to their histological diversity. Management of salivary gland tumours demands detailed knowledge about its anatomy and pathological processes. Most of the salivary gland tumours usually develop at parotid glands, and most of them are benign. Surgical excision is the primary modality for the management of parotid tumours. In certain circumstances, malignant tumours of parotid gland also require adjuvant therapy in addition to surgery. It was a cross-sectional study that was conducted on 30 patients who underwent parotid surgery from January 2021 to January 2023 in the department of ENT and Head-Neck Surgery, Jalalabad Ragib-Rabeya Medical College Hospital. The aim of the present study was to understand the distinct types of parotid tumours, their surgical management, and possible complications. Our study showed 26 (87%) of the parotid tumours were benign; among them, pleomorphic adenoma 19 (71%) was the most common type. Among the malignant tumours, most common type was mucoepidermoid carcinoma 3 (75%). As a part of tumour management, the most common approach to surgery was superficial parotidectomy 21 (70%). Among the patients underwent surgery, 8 (26.7%) developed complications. Parotidectomy can be a very safe approach to tumour management if it is conducted by skilled hand with optimal facilities. Jalalabad Med J 2023; 20 (2): 60-64